Internship Report: Creating Opportunities for Increasing Youth Employment in the Agriculture Sector - Beauchesne, Jean-Frederic; Makungwe, Mirriam (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Zambia’s youth are key development catalysts that have the potential to foster economic prosperity in their communities, when provided with adequate support. As a means to better support Zambia’s youth population, many recent interventions have focused on expanding youth’s access to quality education. However, despite obtaining a higher education, numerous recent university graduates remain unable to qualify for gainful employment opportunities due to their lack of work experience and/or underdevelopment of professional skills. To address young professionals’ skills development gap, EDGE piloted an internship program with Zambian higher education institutions in 2021. Following the successes of EDGE’s pilot intervention, ACDI/VOCA and the International Water Management Institute (IWMI) executed a Partnership Agreement to implement a second, expanded phase of this internship program under the World Bank’s Research Project, Accelerating the Impact of the CGIAR’s Research in Africa (AICCRA)-Zambia. The objective of this joint effort is to connect young professionals to different SMEs over the duration of their specific internship assignments. The program expects interns to assist these private entities with key/priority needs as identified by EDGE and IMWI AICCRA, financial service providers (e.g., commercial banks), third party evaluators and the SMEs themselves. ThisInternship Program supports young entrepreneurs and professionals to gain professional experience, strengthen practical skillsets and, where appropriate, develop competences to intersect research and business, while contributing to the acceleration of IMWI-AICCRA’s Climate Smart Agriculture (CSA) and Climate Information System (CIS) scaling objectives.